Sejarah Sistem Pemerintahan dan Kekuasaan Eksekutif di Indonesia - Khuluqi, Mohammad Ahsanul; Muwahid, Muwahid (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2023)
To understand a legal system, the first thing that must be comprehended is a consensus regarding the history or background of the system's existence. In Indonesia's government system, which adheres to a presidential system, many changes occurred before the amendment to the 1945 Constitution. The government system in Indonesia has shifted from a presidential system where the president is the country's highest leader to a parliamentary system where a prime minister is the head of government. Then, it retook its original feature from a parliamentary system to a presidential system where full command rests with the president as the leader of the state and government. The role of electoral politics was far behind the changes in the dynamics of the legal system. The actual context of government, in this case, the executive, is much simplified and reorganized regarding the existing legal political system. The president, who is part of the key to the highest power in the executive area, oversees various public positions such as ministers and other areas of the executive area.